Improving Discipline and Responsibility of Student Learning Through Project Assessment - Sitti Mania (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2015)
This ‘classroom action research’ aims to determine the effectiveness of the project assessment at Islamic Junior School (Madrasah Tsanawiyah) Model Makassar in the VIII/a class as subject research. The study carried out in two cycles, data collection was done by employing three ways: questionnaires, observation and test administration. The result showed that the project assessment was able to improve: 1) student discipline, shown on average 73,78% of the first cycle and the second cycle was 91,72%. 2) Responsibility for student learning, the average seen in the first cycle of 66,37% and 85,77% for the second cycle. 3) Student learning outcomes, the first cycle were 51,72% while in the second cycle there was 17,24% score below the minimum completeness criteria. On the individual test conducted at the end of the second cycle showed that there are only 4 students (13,79%) who had not reached the minimum completeness criteria.